The Role of Transformastional Leadership, Human Capital, and Job Satisfaction in Influencing Organizaional Citizenship Behavior of Volunteers at The Buddhist Tzu Chi Foundation - Romi Lie; Wylen Djap; Oki Hermawati; Dadang Irawan; Anggaripeni Mustikasiwi (Religi: Jurnal Studi Agama-agama, 2022)
There have been many social foundations in Indonesia in the past few years. The Buddhist Tzu Chi Foundation Indonesia has four humanitarian missions and requires volunteers to give their time, thoughts, and energy to help them achieve their goals. This research was conducted on 62 volunteers in Jakarta, Cikarang, and Bekasi. By using purposive sampling technique and processing using Smart PLS 3.0 to test the hypothesis. The questionnaire results show a positive relationship between transformational leadership, job satisfaction, and organizational citizenship behavior human capital.